إعداد الو سائل على أساس مدونة بلوغسبوت لتر قية مهار ة القراءة لدى طلاب الصف الثامن في المدرسة المتوسطة الحكومية الإسلامية الثانية بميدان - Sri Wahyuni; Samsul Haq (EduInovasi: Journal of Basic Educational Studies, 2024)
Learning media is a tool that will make it easier in a teaching and learning activity. The existence of this media can also help students in learning. Students will also find it easier to increase students' interest in reading skills and teachers to be more creative in providing a material. This research, to improve Blogspot-based learning media in MTsN 2 Medan, while the purpose of developing Blogspot as a learning media has the advantage of making learning for students more interesting, more effective, more flexible, more efficient and directing students to use the internet properly and wisely. and Melvyn I. Where this researcher limits it to 4 steps: 1) Definition ( define ); 2). Design; 3). development; 4). The data collection techniques used are observation, interviews, questionnaires. Meanwhile, data analysis uses spss. The validation results from media experts are with a percentage of 95.2% (very feasible). Based on the results of this study, the use of blogspot-based media also received a positive reaction from 33 students of grade VIII MTsN 2 Medan with a percentage of 90% which showed an increase in students' interest and reading skills in learning Arabic at MTsN 2 Medan. That way, this blogspot media is very feasible to be used in learning Arabic.